Influence of initial cell concentrations on the growth rate and biomass productivity of microalgae in domestic wastewater - Gani, Paran (ALÖKI Kft., Budapest, Hungary, 2016)
The aim of this study was to compare the specific growth rate and biomass productivity of microalgae in domestic wastewater according to the initial cell concentration. The initial microalgae cell concentrations tested started from 103 cell/mL, 104 cell/mL, 105 cell/mL, 106 cell/mL, and 107 cell/mL under outdoor condition. The result revealed that the highest biomass productivity occurred at 106 cell/mL concentration with a value of 1.24 × 104 cell/mL/day, 0.26 day-1 of specific growth rate, and a doubling time of 2.63 days. Meanwhile, the lowest biomass productivity occurred at 103 cell/mL concentration with the lowest specific growth rate of 0.1 day-1 and the longest doubling time, which reached up to 7.14 day. As a result, the initial cell concentration of microalgae did influence the algal biomass productivity and growth rate differently. Thus, the maximum growth rate and biomass productivity were obtained at 106 cell/mL concentration which is recommended to be used in biotechnology industries and any wastewater treatment.